Perkembangan Klasifikasi Massa Batuan Rock Mass Rating: Sebuah Literature Review - Hakim Erlangga Bernado Sakti; Heru Dwiriawan Sutoyo (ReTII, 2022)
Rock mass classification is one of a method to study the quality of rock mass by rating several input parameters, namely: a. Rock physical and mechanical properties; b. Intensity, geometry and condition of discontinuities; c. Ground water conditions; d. Weathering condition; e. Resistance to weathering processes (slake durability index); and f. Special properties of rocks (e.g., swelling and squeezing of claystone, dissolution of limestone). Rock mass rating (RMR) method is the most widely used rock mass classification method. The methodology that used by the author is the literature review. The rock mass classification studied is limited to three types of methods The RMR that has been developed are RMR89, RMR14, and RMR for Cavity Limestone. The basis for choosing the three methods is because based on the initial literature review, the three methods are considered to almost represent the six input parameters needed in the rock mass classification study. RMR14 has included parameters slake durabity index and RMR for cavity limestones have included condition of the cavity in limestone parameters. There are several empirical among the RMR classifications.